Preconceito linguístico: Relação entre os alunos surdos do curso de letras-libras da universidade federal do tocantins, campus de Porto Nacional - Lima, Leidiana de Sousa (Universidade Federal do Tocantins, 2022)
The study presented in this paper talks about linguistic prejudice: the relationship between deaf students in the LIBRAS Literature course at the Federal University of Tocantins, Porto Nacional campus. The general objective is: To analyze the relationship between deaf students in the LIBRAS Literature course at the Federal University of Tocantins, Porto Nacional campus, focusing on linguistic prejudice. And as specific objectives: to investigate if there really exists and how the presence of linguistic prejudice occurs among deaf students in that course; observe whether, in the presence of linguistic prejudice, deaf students experience greater difficulty in the process of acquisition and learning; check if, among deaf students, there is any kind of embarrassment or fear when signaling. Bibliographic research and field research were used as methodologies. The presence of linguistic prejudice among the group of deaf people identified in this study was identified, in addition to some roots that motivate the configuration of such prejudice; which evidenced the need for reflection and construction of new practices on the issue.